The Influence of A Leadership Style and A Compensation Towards the Employees’ Motivation and Performance - Ahmad Darda; Siti Maesaroh; M. Asmi Rizaldy (Kusuma Negara Business School, 2021)
This study is to determine the effect of the leadership style and the compensation on the employees’ motivation and performance. This is the quantitative study using the primary data from the result of questionnaires. There were 98 respondents for the population. The data analysis was the questionnaires and the data process used the statistics software of SmartPLS. 3.0. The result showed that the leadership style significantly influenced the employees’ motivation and performance, whilst the compensation significantly affected the employees’ motivation and performance. The motivation significantly influenced the employees’performance, the leadership style significantly influenced the employees’ performance through the motivation, and the compensation gave a significant effect to the employees’ performance through motivation.